Perancangan Arsitektur Entrprise Perancangan Arsitektur Enterprise SMAN 3 Tulang Bawang Tengah Menggunakan Framework TOGAF ADM: ABSTRAK 1. PENDAHULUAN 2. METODE PENELITIAN 3. HASIL DAN PEMBAHASAN 3.1 Preliminary Phase 3.2 Phase A. Architecture Vision 3.3 Phase B. Business Architecture 3.4 Phase C. Information System Architecture 3.5 Phase D. Technology Architecture 3.6 Phase E. Opportunities Solution 3.7 Phase F. Migration Planning 4. KESIMPULAN 5. SARAN UCAPAN TERIMA KASIH DAFTAR PUSTAKA - Minarni, Minarni; Wasilah, Wasilah (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
In improving the quality of efficiency and effectiveness in educational organizations, it is necessary to carry out long-term strategic planning of information systems and information technology (IS/IT) that are appropriate to support performance and productivity in an educational institution. SMAN 3 TBT is a school that utilizes/uses IS/IT in the process of supporting its operations. However, this school is one of the senior high schools that has not fully implemented and utilized IS/IT architectural planning in its business processes. In general, it is still run manually or only utilizes Microsoft Office and Google/Internet in its business processes, so there is no data integration and it is less efficient. Therefore, it is necessary to have a strategic plan in designing an enterprise architecture that can harmonize the development of information systems and existing information technology with the organization's business processes at SMAN 3 TBT. TOGAF ADM for its Enterprise Architecture, which contains the stages from the preliminary phase to migration planning, is the framework chosen for this research. Blueprints for IS/IT strategic planning including business architecture, data architecture, application architecture, technology architecture, and recommended technological advances, are the results/outputs of this research. Kata kunci— TOGAF ADM, framework, arsitektur enterprice, proses bisnis